Translocation of a polymer through a nanopore starting from a confining nanotube. Issue 5 (2nd February 2015) - Sean, David; de Haan, Hendrick W.; Slater, Gary W.; Gaš, Bohuslav
<x xml:space="preserve">Abstract</x> In this manuscript, Langevin Dynamics simulations and Tension‐Propagation theory are used to investigate the forced translocation of a polymer from a confining tube through a nanopore situated at one of the tube's ends. The diameter of the tube allows for a control over the polymer conformations: decreasing the tube diameter reduces the number of conformations available to the polymer chain both before and during translocation. As the tube diameter is decreased, the translocation time is observed to increase. Interestingly, while the width of the distribution of translocation times is reduced if the chain starts in a tube, it reaches a maximum for weakly confining tubes. A Tension‐Propagation approach is developed for the tube‐nanopore setup in the strongly driven limit. Good agreement between the simulations and the theory allows for an exploration of the underlying physical mechanisms, including the calculation of an effective pore friction and the assessing of the impact of monomer crowding on the trans side.